Molecular dynamics simulations reveal ligand-controlled positioning of a peripheral protein complex in membranes - Steven M. Ryckbosch (Nature Portfolio, 2017)
Natural supplies of bryostatin, a compound in clinical trials for Alzheimer’s disease, cancer, and HIV, are scarce. Here, the authors perform molecular dynamics simulations to understand how bryostatin interacts with membrane-bound protein kinase C, offering insights for the design of bryostatin analogs.